2015
DOI: 10.1021/cm504572b
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxic Carbon Dots Potently Inhibit Human Insulin Fibrillation

Abstract: One prevention and therapeutic strategy for diseases associated with peptide or protein fibrillation is to inhibit or delay the fibrillation process. Carbon dots (C–Dots) have recently emerged as benign nanoparticles to replace toxic quantum dots and have attracted great attention because of their unique optical properties and potential applications in biological systems. However, the effect of C-Dots on peptide or protein fibrillation has not been explored. In this in vitro study, human insulin was selected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
162
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(167 citation statements)
references
References 40 publications
4
162
0
1
Order By: Relevance
“…Our experiments demonstrated that these CDs strongly inhibit human insulin fibrillation in a concentration-dependent manner [21]. Increasing the concentration of CDs enhances the inhibiting effect.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Our experiments demonstrated that these CDs strongly inhibit human insulin fibrillation in a concentration-dependent manner [21]. Increasing the concentration of CDs enhances the inhibiting effect.…”
Section: Discussionmentioning
confidence: 59%
“…On the contrary, the presence of the DHLA-CDs in this study promotes human insulin fibrillation in a concentration-dependent manner. One has to point out that the DHLA-CDs have completely different nature in terms of size, surface property and component from those we reported in Reference [21]. As displayed in Figure 2D and 2E, the size of the DHLA-CDs is much larger (i.e.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations